Chititra Banerji: The Hour of the Goddess. Memories of Women, Food and Ritual in Bengal - Davidson, Alan (Petits Propos Culinaires, 2024)
Chititra Banerji: The Hour of the Goddess. Memories of Women, Food and Ritual in Bengal: Seagull Books, Calcutta, 2001: ISBN 81-7046-183-9: 120 pp., b/w photos. by Naveen Kishore, h/b, Rupees 475.